Extreme values and financial risk - Stephen Chan; Saralees Nadarajah (MDPI, 2018)
Since the 2008 financial crisis, modeling of the extreme values of financial risk has become important. Postgraduate programs and PhD research programs in mathematical finance are cropping up in nearly every university. Additionally, many conferences are being held annually on the topic of extreme financial risk. The aim of this Special Issue is to provide a collection of papers from leading experts in the area of extreme financial risk.
Keywords: 330